Invisible - Gonzalez, Christina Diaz, 1969-; Epstein, Gabriela (New York, NY : Graphix, an imprint of Scholastic, 2022)
How can you be yourself when no one sees the real you? Five students meet in the school cafeteria when they're forced to complete their school community service hours. There's George: the brain, Sara: the loner, Dayara: the tough kid, Nico: the rich kid, and Miguel, the jock. They immediately know that they have nothing in common with each other even though their school administration has decided that they all belong together. None of the kids wants to be there, and each has their own issues they're dealing with in their life outside of school. But when they encounter someone who truly needs their help, they might just be able to come together to work as a team and help their community after all.
3-6
GN260L
2.9
OBOB MS 2023-2024
Keywords: Middle school students -- Comic books, strips, etc; Middle school students -- Fiction; Friendship -- Comic books, strips, etc; Friendship -- Fiction; Graphic novels; Hispanic Americans -- Fiction; Comics (Graphic works)